1990
DOI: 10.1111/j.1365-2044.1990.tb14492.x
|View full text |Cite
|
Sign up to set email alerts
|

Accidents, near accidents and complications during anaesthesia A retrospective analysis of a 10‐year period in a teaching hospital

Abstract: SummaryA retrospective analysis is presented of all reports of faults, accidents, near accidents and complications associated with anaesthesia in one hospital from 1978 to 1987. 113 074 anaesthetics were administered in that period, of which 97496 were for noncardiac procedures. There were 148 reports; 39 were of dental damage. Peri-operative cardiac arrests during noncardiac surgery were reported 29 times. Sixteen of these were fatal. Anaesthesia was thought to havc played an important role in 13 cardiac arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
7

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 9 publications
1
70
0
7
Order By: Relevance
“…[35][36][37][38][39][40][41][42] This partly reflects the role of actual equipment failure, reported to occur in 15-20% of the procedures, but probably also refers to overall quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42] This partly reflects the role of actual equipment failure, reported to occur in 15-20% of the procedures, but probably also refers to overall quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…1 The reported frequency of intraoperative cardiac arrest varies widely, from 2.56 to 39 cases per 10,000 operations. [1][2][3][4][5][6] However, it is difficult to assess the quality of cardiopulmonary resuscitation (CPR) because of an absence of standardized templates for describing resuscitation efforts and for classifying the intraoperative complexity of such cases. Furthermore, limited data are available regarding the predictors of CPA survival and 30-day clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies on drug errors in anesthesia have not classified the type of drug errors, 5 been small in numbers, or based on voluntary anonymous incident reports. [6][7][8] This latter method of study has been shown to capture only a small fraction of adverse drug events. [9][10][11] Thus, the real magnitude, or incidence, of drug errors in anesthesia practice is not known.…”
mentioning
confidence: 99%